2020
DOI: 10.3390/cancers12040814
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of an MRI-Derived Radiomics Model to Predict Biochemical Recurrence after Surgery for High-Risk Prostate Cancer

Abstract: Adjuvant radiotherapy after prostatectomy was recently challenged by early salvage radiotherapy, which highlighted the need for biomarkers to improve risk stratification. Therefore, we developed an MRI ADC map-derived radiomics model to predict biochemical recurrence (BCR) and BCR-free survival (bRFS) after surgery. Our goal in this work was to externally validate this radiomics-based prediction model. Experimental Design: A total of 195 patients with a high recurrence risk of prostate cancer (pT3-4 and/or R1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(75 citation statements)
references
References 42 publications
5
68
2
Order By: Relevance
“…It had correctly demonstrated that patient with high-risk PCa had signi cantly worse BCR-free survival compared with low-to intermediate-risk groups [28,29]. Results from some studies indicated that imaging ndings such as PI-RADS and radiomics features had prognostic value on BCR after prostatectomy [30,20,31]. Our preliminary results also showcase the PI-Risk strati cation even revealed a potential role in predicting the prognostic of disease progression risk preoperatively.…”
Section: Discussionsupporting
confidence: 55%
“…It had correctly demonstrated that patient with high-risk PCa had signi cantly worse BCR-free survival compared with low-to intermediate-risk groups [28,29]. Results from some studies indicated that imaging ndings such as PI-RADS and radiomics features had prognostic value on BCR after prostatectomy [30,20,31]. Our preliminary results also showcase the PI-Risk strati cation even revealed a potential role in predicting the prognostic of disease progression risk preoperatively.…”
Section: Discussionsupporting
confidence: 55%
“…It had correctly demonstrated that patient with high-risk PCa had signi cantly worse BCR-free survival compared with low-to intermediate-risk groups [28,29]. Results from some studies indicated that imaging ndings such as PI-RADS and radiomics features had prognostic value on BCR after prostatectomy [20,30,31]. Our preliminary results also showcase the PI-Risk strati cation even revealed a potential role in predicting the prognostic of disease progression risk preoperatively.…”
Section: Discussionsupporting
confidence: 55%
“…Thus, radiomics has successfully introduced to discriminate benign and malignant lesions [ 8 ], predict aggressiveness [ 9 ] and estimate Gleason scores [ 10 ]. However, there were still few studies focusing on BCR prediction for patients after radical prostatectomy with relatively large amount datasets [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%